Optimisation of an HHG-seeded harmonic cascade FEL design for the NLS project - Dunning, D; Thompson, N; McNeil, B; Bartolini, R; Huang, Z; Geng, H (2010)
Optimisation studies of an HHG-seeded harmonic cascade FEL design for the UK's proposed New Light Source (NLS) facility [1] are presented. Three separate FELs are planned to meet the requirements for continuous coverage of the photon energy range 50-1000 eV with variable polarisation, 20 fs pulse widths and good temporal coherence. The design uses an HHG seed source tuneable from 50-100 eV to provide direct FEL seeding in this range, and one or two stage harmonic cascades to reach the higher photon energies. Studies have been carried out to optimise a harmonic cascade FEL operating at 1 keV; topics investigated include modulator configuration, seed power level and effects of the HHG seed structure. FEL simulations using realistic electron beam distributions are presented and tolerance to increased emittance has been considered.